2020
DOI: 10.3390/biom11010002
|View full text |Cite
|
Sign up to set email alerts
|

Molecules, Mechanisms, and Disorders of Self-Domestication: Keys for Understanding Emotional and Social Communication from an Evolutionary Perspective

Abstract: The neural crest hypothesis states that the phenotypic features of the domestication syndrome are due to a reduced number or disruption of neural crest cells (NCCs) migration, as these cells differentiate at their final destinations and proliferate into different tissues whose activity is reduced by domestication. Comparing the phenotypic characteristics of modern and prehistoric man, it is clear that during their recent evolutionary past, humans also went through a process of self-domestication with a simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 240 publications
(324 reference statements)
2
24
0
Order By: Relevance
“…The individual recognizes fear in oneself as an internal experience, and in others as external associated manifestations, such as freezing, escaping, trembling, frightened facial expressions, etc. In evolutionary terms, fear is associated with the activation of neural circuits responsible for survival [10]. Fear conditioning is an example of associative learning, a process by which the brain creates memories about the relationship between two events (Figure 4).…”
Section: Higher-order Theory Of Consciousness and Fear Conditioningmentioning
confidence: 99%
See 3 more Smart Citations
“…The individual recognizes fear in oneself as an internal experience, and in others as external associated manifestations, such as freezing, escaping, trembling, frightened facial expressions, etc. In evolutionary terms, fear is associated with the activation of neural circuits responsible for survival [10]. Fear conditioning is an example of associative learning, a process by which the brain creates memories about the relationship between two events (Figure 4).…”
Section: Higher-order Theory Of Consciousness and Fear Conditioningmentioning
confidence: 99%
“…Optimal emotion regulation is thought to arise from the balance between the PFC and amygdala activity [168]. Stress negatively affects this activity of the PFC, which explains why a strategy of cognitive reappraisal in real-life situations is often ineffective [10].…”
Section: Connections Of the Amygdalamentioning
confidence: 99%
See 2 more Smart Citations
“…ASD varies in degrees of severity, occurring in 1% of the population, and its prevalence has been increasing during the last three decades (Maenner et al, 2020). The causes of different subtypes of autism lay in the complex landscape of environmental, genetic and epigenetic influences (Waye and Cheng, 2018;Šimić et al, 2020). Although the etiology of most cases of ASD is still unknown, numerous studies have shown that there is a strong heritable component.…”
Section: Introductionmentioning
confidence: 99%